Evaluation of utility of immunohistochemistry markers as a tool for objective diagnosis of low-grade myelodysplastic syndrome in routine reporting: Prospective observational study - Richa Juneja; Haraprasad Pati; Prasad Dange; Gopila Gupta; Manoranjan Mahapatra; Seema Tyagi; Renu Saxena (Wolters Kluwer Medknow Publications, 2022)
Purpose: Diagnosis of myelodysplastic syndrome (MDS) primarily relies on the detection of morphological dysplasia in bone marrow. It is subjective and many studies have reported lack of interobserver agreement in reporting. Biopsy is preferred specimen for megakaryocyte assessment. We studied 43 bone marrow biopsies from 40 suspected MDS patient having persistent undiagnosed cytopenia. Utility of immunohistochemistry (IHC) with CD61 and p53 in detecting low-grade MDS was analyzed over routine morphology. Method and Results: Total number of megakaryocytes and number of dysplastic megakaryocytes seen on CD61 IHC was significantly higher than that on H and E stain (P value < 0.05) Out of total 43 biopsies, 13 [30.2%] cases showed dysplastic megakaryocytes that were confirmed by interobserver agreement after IHC. From 30 cases with no significant dysplasia on morphology, 21/43 [48.8%] cases showed >10% dysplastic megakaryocytes on CD61 (P value 0.0001). Nine cases showed no significant dysmegakaryopoiesis with either H and E or CD61 IHC. Fourteen cases could meet higher cut off (30%) of dysmegakaryopoiesis with CD 61 IHC. Out of total 34 cases showing significant dysplasia 7 cases (20.6%) showed positivity for p53 on IHC, which is little less than that reported in low-grade MDS. Conclusion: CD61 IHC is helpful in making correct diagnosis of MDS in cases with minimal dysplasia and should be performed before excluding possibility of MDS on morphology in a patient with undiagnosed cytopenia. IHC is cost effective tool for MDS diagnosis in developing world where access to extensive flow cytometery and molecular testing is limited.